A Reconceptualization of Marine Security Institutions to Make Indonesia Become a Maritime Axis Country - Chalid Darmawan; Rudiyanto Rudiyanto; Bayu Asih Yulianto (Faculty of Social Science, Universitas Negeri Padang, 2022)
This research goal is to discover the idea of delivery safety companies in Indonesia these days and reconnect the best maritime safety establishments to underpin the life of Indonesia as a rustic with a maritime axis. This research makes use of the regulation research methods. Text is performed via way of means of checking the library data, with inside the shape of laws, books, articles, and journals and is different. This research uses SWOT analysis. The result of research suggests that currently, companies worried about safety in Indonesia can not feature successfully due to the fact there are too many enterprise companies that have interests, the life of the Maritime Safety Authority, which does now no longer have no precise authority, nor overlapping jurisdiction among establishments. Reconceptualization of maritime safety establishments had to be performed via way of means of growing and enhancing the popularity of Water Police to Maritime Police as a perfect shape of maritime safety